Influence of Transformational and Transactional Leadership Towards Employee Performance (Study at PT Ekistindo, Makassar) - Idayanti Nursyamsi S. (Jurnal Aplikasi Manajemen, 2011)
The purpose of this study was to analyze (1) the significances of the transformational leadership and transactional leadership to employee’s performance, and (2) the dominant variable affecting employee’s performance. From the sample that consisted of 102 respondent, the analysis used multiple linear regression to determine a model which best predicts the performance of these firms. Result of this research shown that transformational and transactional leadership variables have significant effect on the employee’s performance, and that transformational leadership is the most dominant variable affecting employee’s performance.Keywords: transactional leadership, transformational leadership, performance